Kehujjahan Hadis Wasiat dalam Upaya Reaktualisasi Hukum Islam - Hafisuddin; Khairul Bahri Nasution (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This article explains the custom of Indonesian society that many parents, when they are still alive, say the sentence to give land, rice fields or houses to their children. This sentence has caused differences in understanding. Some people interpret it as a will that must be carried out after a parent dies, while other people understand it not as a will, but as a form of "resignation" or appointment by parents of a share of the inheritance for their children. This different understanding arises from the knowledge of the hadiths which discuss wills, the limits of who is allowed to give a will, and who is not entitled to receive a will. This study is a literature review with reference to related journals, articles and books. The results of the study show that one of the hadiths regarding wills was narrated by Muslim from Ibn Umar, whose editorial is: "It is not halal for a Muslim to spend two nights, even though he has something that he must will, unless the will is written on his side." This hadith is an authentic hadith which was also narrated by al-Aimmah as-Sittah. Likewise, the hadith regarding wills is only 1/3 also an authentic hadith which was narrated by al-Aimmah as-Sittah. Meanwhile, the hadith regarding 'there is no will for heirs ' is also narrated by three of our Sunan authors except an-Nasai. Tirmidhi validated some of these hadith lines and hashed them. Even Muhammad Ja'far al-Kattani classifies it as a Mutawatir hadith in Nazham al-Mutanatsir Min al-Hadith al-Mutawatir. One form of legal reform effort related to the issue of wills is the implementation of mandatory wills for grandchildren as substitute heirs, children or adoptive fathers, and non-Muslim heirs.